Post-Dilatation of New-Generation Self-Expandable Transcatheter Aortic Valves Does Not Increase Atrioventricular Conduction Abnormalities - Grégoire Massoullié; Nicolas Combaret; Géraud Souteyrand; Jean Pascal Salazard; Bruno Pereira; Frédéric Jean; Pascal Motreff; Ouarda Taghli-Lamallem; Guillaume Clerfond; Romain Eschalier (Diagnostics, 2023)
The impact that post-dilatation has on the risk of experiencing conduction disorders after post-transcatheter aortic valve replacement with self-expanding valves (SE-TAVR) is unclear. We compared the rate of developing an atrioventricular (AV) high-grade conduction disorder and permanent pacemaker implantation (PPI) in post-TAVR patients undergoing post-dilatation. We enrolled patients with severe symptomatic calcified aortic stenosis (CAS) who were undergoing SE-TAVR between 1 January 2016, and 19 April 2019 at a single French center. Of the 532 patients treated with SE-TAVR, 417 subjects (78.4%) received Corevalve Evolute R and 115 subjects (21.6%) received the latest-generation Corevalve Evolute Pro valve. In total, 104/532 patients (19.5%; 21.6% with Evolute R vs. 12.2% with Evolute Pro, p = 0.024) required post-dilatation. Evolut R was associated with an increased risk of post-dilatation (odds ratio 2.1 (1.01–4.33, p = 0.046)). We did not observe any post-dilatation increases in AV or in intra- and interventricular conduction disorders. In total, 26.1% of participants needed PPI within the first 30 post-procedure days (p = 0.449). Post-dilatation was not associated with a higher PPI risk (subdistribution hazard ratio 1.033 (0.726–1.471); p = 0.857). No significant differences existed between the groups in terms of one-year mortality (10.3%; p = 0.507). Post-dilatation in SE-TAVR did not increase the rate of electrical conduction disorders and PPI in the early implantation phase. The latest generation of SE-TAVR valves was associated with less need for post-dilatation.